2016
DOI: 10.14210/rtva.v19n1.p5-30
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição Do Estudo Das Características Culturais Do Cluster Da Malacocultura Da Grande Florianópolis Para a Gestão Das Atividades De Turismo Na Região

Abstract: No Brasil, no Estado de Santa Catarina, na Grande Florianópolis, encontra-se o cluster da malacocultura, formado por micro e pequena empresas e por produtores autônomos. Embora tenha condições ambientais e econômicas favoráveis, este cluster apresenta problemas de gestão que estão relacionados com o comportamento dos seus integrantes refletido na sua maneira de ser, de agir e de pensar, condicionada pela sua cultura, que afetam a sua competitividade. Será que estas mesmas características culturais locais seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
0
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
(8 reference statements)
2
0
0
4
Order By: Relevance
“…The testimonies we found are controversial. However, the work of Teixeira et al (2017) corroborates the hypothesis, as they found that the mariculture cluster in the Greater Florian opolis region is influenced by the local culture, predominantly of Azorean origin, with strong traits of individualism, tolerance for uncertainty, indulgence, short-term orientation and idleness. According to Ndubisi (2011), culture plays a subtle, yet powerful role in influencing people's social behaviours and, in our case, there is evidence to suggest that the culture of the stakeholders should not be ignored in trying to understand and model the drivers of trust in the relationship among the authors of the supply chain (Leidner and Kayworth, 2006).…”
Section: Trust For Sustainable Agri-food Productionsupporting
confidence: 59%
“…The testimonies we found are controversial. However, the work of Teixeira et al (2017) corroborates the hypothesis, as they found that the mariculture cluster in the Greater Florian opolis region is influenced by the local culture, predominantly of Azorean origin, with strong traits of individualism, tolerance for uncertainty, indulgence, short-term orientation and idleness. According to Ndubisi (2011), culture plays a subtle, yet powerful role in influencing people's social behaviours and, in our case, there is evidence to suggest that the culture of the stakeholders should not be ignored in trying to understand and model the drivers of trust in the relationship among the authors of the supply chain (Leidner and Kayworth, 2006).…”
Section: Trust For Sustainable Agri-food Productionsupporting
confidence: 59%
“…Essa resistência pode ser entendida como reflexo do individualismo, característica comportamental comum aos nativos de Florianópolis, de origem açoriana. Em estudo sobre a competitividade do cluster da malacocultura existente no município, Teixeira (2016) e Teixeira et al (2017) apontam o individualismo como um dos fatores que afetam a dinâmica e a competitividade desta organização produtiva. Da mesma forma como no cluster, também nos projetos de TBC de Florianópolis o individualismo tende a afetar os seus resultados, uma vez que reflete na capacidade de cooperar e de colaborar dos integrantes, que é fundamental nesse tipo de iniciativa.…”
Section: Resultsunclassified
“…No que se referem aos clusters, as especificidades culturais locais podem favorecer ou desfavorecer essa forma de organização produtiva pelo que pode implicar sobre as relações sociais e comunitárias. A cultura exerce influência sobre a governança endógena, sobre a gestão dos negócios e, consequentemente, sobre a competitividade de clusters (Teixeira, 2016;Teixeira et al, 2017).…”
Section: Clusterunclassified
See 1 more Smart Citation
“…Esse modelo epistemológico de Governança Pública representa o viés stakeholders (MEDIOTTE et al, 2018;EMMENDOERFER et al, 2016;TEIXEIRA;GOMES, 2019), isto é, compete à composição de agentes não públicos e aos atores responsáveis pela formulação de políticas públicas e quaisquer outros aspectos e soluções de problemas que incumbem a estes deliberarem (BANCO MUNDIAL, 1994).…”
Section: Governança Pública No Turismounclassified